2017
DOI: 10.3390/nu9111202
|View full text |Cite
|
Sign up to set email alerts
|

Direct Feeding at the Breast Is Associated with Breast Milk Feeding Duration among Preterm Infants

Abstract: Background: In spite of high rates of initiating breast milk feeding (BMF) among preterm infants, a significant rate of discontinuation occurs shortly after discharge. Aim: To investigate the effect of mode (direct feeding at the breast vs. expressing) and exclusivity (breast milk combined with formula vs. breast milk only) as well as maternal perceptions on the duration of BMF among preterm infants. Methods: The study included mothers whose infants were born before 32 weeks gestation, between January 2012 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 59 publications
6
36
1
1
Order By: Relevance
“…Our finding that exclusive as opposed to mixed breastfeeding at discharge was strongly related to the probability of continuation points to a modifiable practice that likely reflects unit policies, as rates of mixed versus exclusive feeding at discharge vary widely across Europe (Wilson et al, ). In contrast, we did not find that direct feeding from the breast had a significant impact on continuation, unlike a study conducted in one single‐centre in Israel on 162 mothers of very preterm infants (Pinchevski‐Kadir et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that exclusive as opposed to mixed breastfeeding at discharge was strongly related to the probability of continuation points to a modifiable practice that likely reflects unit policies, as rates of mixed versus exclusive feeding at discharge vary widely across Europe (Wilson et al, ). In contrast, we did not find that direct feeding from the breast had a significant impact on continuation, unlike a study conducted in one single‐centre in Israel on 162 mothers of very preterm infants (Pinchevski‐Kadir et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…The rationales for this choice were based on the fact that breastfeeding at the breast is the norm in Iceland, where national data show a 98% initiation rate of term infants (Directorate of Health, 2012). The other reason was that previous studies have shown that mothers that exclusively express breast milk do so for a shorter time compared with mothers that exclusively feed their infant at the breast (Forster et al, ; Pang et al, ; Pinchevski‐Kadir et al, ). It has also been reported that mothers that combine breastfeeding at the breast and formula feeding have a shorter breastfeeding duration than mothers that exclusively breastfeed at the breast (Holmes, Auinger, & Howard, ).…”
Section: Discussionmentioning
confidence: 99%
“…As we learn more evidence in support of breastfeeding mothers with hospitalized newborns better survival will have these patients [25].…”
Section: Resultsmentioning
confidence: 99%